LACK OF EFFECTIVE COMMUNICATION AMONG YOUNG PEOPLE AS A CAUSE OF DISAGREEMENT - Aymuratova Zliyxa Janabay qızı (TADQIQOTLAR, 2026)
Abstract: Effective communication is a fundamental skill necessary for maintaining healthy interpersonal relationships. Among young people, the lack of effective communication has increasingly become a significant cause of disagreements in schools, families, peer groups, and online spaces. This article explores how poor communication skills—such as inability to express emotions clearly, poor listening habits, misuse of digital communication, and lack of conflict-resolution skills— contribute to misunderstandings and conflicts among young people. The study highlights the role of emotional development, social influences, and modern technology in shaping communication patterns. By examining the causes and effects of ineffective communication, the article emphasizes the importance of teaching communication skills to reduce disagreements and promote mutual understanding among youth.